Evaluation of Coaching Students Based on Dormitory Curriculum in Madrasah Aliyah Negeri Insan Cendikia Bengkulu Tengah - Emilda Sulasmi (BIRCU, 2020)
When BJ Habibie became the head of the BPPT, the idea of establishing a boarding school-based madrasa was based on the basic concept of the integration of Faith and Taqwa (IMAQ) and Science and Technology (IPTEK) called Madrasah Aliyah Negeri Insan Cendikia in Serpong, then this model developed to various provinces one of which is Bengkulu Province. The problem is the model developed by Madrasah Aliyah Negeri Cendikia Insane already running optimally and optimally, the extent of the success of student coaching in the Dormitory at Madrasa Aliyah Negeri Cendikia Insan Bengkulu Tengah. Therefore, this study discusses the evaluation of the management of student coaching in MAN Insan Cendikia Bengkulu Tengah Boarding House.The research method used is descriptive qualitative with evaluative research type, this research was conducted at Madrasah Aliyah Negeri Insan Cendikia Bengkulu Tengah, research data sources consisted of Boarding Trustees and Students. The results showed that all components and curricula of curriculum consisting of Salimul Aqidah, Sahihul Ibadah and Moral Karimah had been carried out well and fulfilled the established curriculum requirements for curriculum. Some of the obstacles experienced by hostel caregivers are heterogeneity of students from various aspects, but overcoming this the manager uses two approaches, namely the regulative approach and the psychological approach.